The PERBANDINGAN EFEKTIVITAS AIR PERASAN JERUK NIPIS (Citrus aurantifolia) DAN BELIMBING WULUH (Averrhoa blimbi L) DALAM PEMERIKSAAN HITUNG JUMLAH LEUKOSIT - Anggraeni Sih Prabandari; Ajeng Novita Sari; Mening Sri Darwati (LPPM Universitas Abdurrab, 2024)
Juice of lime (Citrus aurantifolia) and starfruit (Averrhoa blimbi L) contain citric acid which has the same characteristics as glacial acetic acid in Turk's solution. This study was carried out to determine the potential of them as a substitute for glacial acetic acid in the leukocyte count and compare it with Turk's solution as a standard. We used three variations of concentration, namely 1%, 2% and 3%. The specimen used was venous blood with EDTA anticoagulant which was examined using an improved Neubauer counting chamber. The result showed average number of leukocytes calculated using a solution of star fruit and lime at a concentration of 1% was 6287 cells/mm3 vs 4537 cells/mm3, a concentration of 2% was 3525 cells/mm3 vs 3387 cells/mm3 and at a concentration of 3% was 2775 cells/mm3 vs 3225 cells/mm3. The number of leukocytes in the control (Turk's solution) was 7050 cells/mm3. Starfruit juices with a concentration of 1% gave the results closest to the control. Based on the results of the one-way ANOVA test, the sig value was 0.000 (p<0.05) and the independent t-test showed a value (p>0.05), which means that there was no difference in the number of leukocytes examined with Turk's solution and modified starfruit solution. We concluded, starfruit juices with a concentration of 1% was recommended as a substitute for Turk's solution than lime juice.